MOBILITY OF NURSING SPECIALISTS FOR THE IMPROVEMENT OF THEIR PROFESSIONAL SKILLS AND COMPETENCIES - Aneta Dokova; Silviya Borisova; Todorka Kostadinova; Svetlana Panayotova (Peytchinski Publishing, 2018)
Purpose: The purpose of this study is to follow-up the development of the students' and teachers' mobilities within "Erasmus+" and the impact of the training on their professional skills and competences. Material and methods: The study covers the period 2011-2018 in which Medical University "Prof. Paraskev Stoyanov" of Varna organized a total of 78 mobilities according to 19 "Erasmus+" agreements for mobilities of students and teachers from the Faculty of Public Health, 9 agreements for students in the specialty of nursing, 7 "Erasmus+" agreements for students in the specialty of midwifery, and 3 agreements for bilateral academic cooperation with partner universities. After the completion of the mobilities, the students' answered the questionnaire accompanying their final report, in which they give their feedback and evaluation of the fulfilled practices. Results: The students' and teachers' mobilities in the specialties of nursing and midwifery are presented by specialty, number and countries. An analysis is provided of the feedback and evaluation of the participants in the mobilities about the benefits related to their professional qualification and future career. Recommendations are made for an adequate response of the university education and the professional challenges in front of the future nurses and midwives. Conclusion: The increased interest to the participation in mobilities by the students of nursing care is evidence of their motivation to improve their professional skills and competences and is a prerequisite for a better quality of health care in Bulgaria as well as competitiveness within the European Union.